Profile of confirmed and symptomatic cases of COVID-19 that progressed to recovery without hospitalization in a Northeastern brazilian municipality (Research, Society and Development, 2022)
Objective: to describe the clinical-epidemiological profile of confirmed and symptomatic cases of COVID-19 in a municipality in the Brazilian Northeast, which in turn progressed to recovery without hospitalization. Method: an ecological study of secondary data analysis of the Ministry of Health's eSUS-VE and FormSUS of the Municipal Health Department of São Cristóvão, Sergipe, Brazil. We evaluated 1,098 symptomatic people with a positive report for COVID-19 between April and August 2020, who in turn progressed to recovery without hospitalization, either in infirmary beds and/or ICU. Results: the mean age of recovered cases without hospitalization was 38.6 years and the majority were female (59.1%). The most prevalent symptoms were headache (62.7%; n= 688), cough (60.7%; n= 666) and fever (53.4%; n= 586). More than half had up to three simultaneous symptoms (65.3%). Dyspnea was the least reported symptom (19.9%). Only 22.6% had comorbidities, the most common being arterial hypertension and diabetes. Conclusion: there was a predominance of young people and adults without comorbidities among mild cases of COVID-19 who progressed to recovery without hospitalization.